Economic evaluation of the chronic hepatitis B treatment strategies in Italy - Iannazzo, Sergio; Coco, Barbara; Brunetto, Maurizia; Rossetti, Francesca; Caputo, Antonietta; De Francesco, Maria; Bonino, Ferruccio (Farmeconomia. Health economics and therapeutic pathways, 2013)
BACKGROUND AND OBJECTIVE: Pharmacological approaches available in chronic hepatitis B (CHB) are based on 48-weeks finite course of peg-interferon (PEG-IFN) or continuous administration of nucleoside analogues. Recent studies gave way to early identification of non-responders to peg-interferon with a stopping rule based on virologic/serologic markers at week 12. A pharmacoeconomic simulation model was developed to support the economic evaluation of HBeAg-negative CHB treatment strategies, which either involve first line peg-interferon with stopping rule and switch to current most effective analogue entecavir or tenofovir, or nucleosides analogues in first line treatment. This model showed a good cost-effectiveness profile of the first line treatment with peg-interferon. Aim of the present study was the estimation of the impact of a wide adoption of a first line with PEG-IFN and the stopping rule on total overall cost related to CHB over the lifetime of patients in Italy. METHODS: The Markov model was developed to perform a lifetime simulation of the disease progression considering the following health-related states: active CHB, virologic response, HBsAg clearance, compensated cirrhosis with active CHB, compensated cirrhosis with virologic response, decompensated cirrhosis, hepatocellular carcinoma, liver transplant, post-liver transplant and death. The outcomes provided by the model were average survival, quality-adjusted life years (QALY) and costs, calculated from the Italian National Health Service (SSN) perspective. A “current” mix of treatments, where 80% patients received ETV or TDF in first-line, was compared with an “hypothetical” mix defined by a 100% adoption of a PEG-IFN first-line with the stopping rule, to estimate the impact on total lifetime CHB-related costs for a cohort of 100 HBeAg-negative CHB patients in Italy. RESULTS: Results obtained from the evaluation of overall total treatment cost over patients’ lifetime appeared to confirm the cost-effectiveness of peg-interferon previously assessed. Lifetime overall total cost resulted significantly lower with the “hypothetical” treatment mix as compared to the “current” mix.. In fact, estimated lifetime overall total costs for the former and latter scenario were equal to €7,239,050 and €9,060,150 respectively, thus generating a saving of approximately 20% associated to CHB treatment with first-line peg-interferon. CONCLUSION: Based on the results obtained from the economic evaluation of the CHB treatment strategies, first-line peg-interferon associated with the stopping rule and switch to nucleoside analogues consistently represents a convenient strategy on both the clinical and economic perspective.